Pete the cat's train trip - Dean, James, 1957- (New York, NY : Scholastic, Inc., 2016)
"All aboard! Pete the Cat can't wait to visit Grandma, especially because he gets to take a groovy train ride to see her."--Page 4 of cover.
Ages 4-8.
Guided reading level: H.
Accelerated Reader
Accelerated Reader AR
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Railroad travel -- Juvenile fiction; Cats -- Juvenile fiction; Readers (Primary); Fiction